Coconut conservation and propagation - Wilms, Hannes; Bazrafshan, Amirhossein; Panis, Bart; Adkins, Steve W. (2024)
The conservation of coconut genetic resources is essential for the industry to thrive. For thousands of years, people have adapted to new situations by breeding crops; however, breeding programmes rely on the diversity present within a species – diversity that is, in the case of coconut, under threat. To conserve coconut diversity, both in situ and ex situ approaches have been developed. For in situ conservation, on-farm conservation has been implemented as well as protecting areas containing wild coconut palms. These methods allow some natural adaptation over time but are generally not accessible to other farmers or breeders, so gene banks play an important role. To date, field collections have been the main coconut conservation method, but these collections face challenges, so complimentary in vitro alternatives are being developed. This chapter tackles all coconut conservation methods and gives an overview of the benefits, drawbacks and complementary approaches.